Cranial anatomy of the aetosaur Paratypothorax andressorum Long & Ballew, 1985, from the Upper Triassic of Germany and its bearing on aetosaur phylogeny - Schoch, Rainer R. (2016)
The large aetosaur Paratypothorax andressorum has so far been known only by its osteoderms. Here we describe for the first time the skull of a complete, articulated specimen of this taxon that was found in the type horizon at Murrhardt, southwestern Germany. Paratypothorax andressorum has the following cranial autapomorphies: (1) upper jaw margin with deep notch between premaxilla and maxilla, (2) maxilla-lacrimal suture with finger-like projection, (3) upper temporal fenestra triangular, and (4) first paramedian cervical osteoderms narrow and oval, much smaller than second row. Apart from these features, the skull of P. andressorum closely resembles that of the small aetosaur Aetosaurus ferratus known from the same horizons, despite major differences in the morphology of osteoderms. Both taxa share (1) the pointed, beak-shaped premaxilla which expands only gently anterior to the nasal, (2) maxilla and lacrimal excluding jugal from margin of antorbital fenestra, (3) exclusion of squamosal from margin of infratemporal fenestra, and (4) posterior part of jugal not downturned. Phylogenetic analysis reveals poorly resolved relationships within Aetosauria, but exclusion of a problematic taxon Coahomasuchus results in a much better resolution, with Paratypothorax to nest with Rioarribasuchus, Tecovasuchus, Typothorax, and Redondasuchus within a monophyletic Typothoracinae. Interestingly, Aetosaurus and Stenomyti form successive sister taxa of this clade rather than fall within an aetosaurine grade of basal aetosaurs, as suggested by previous authors.The resemblance of Paratypothorax and Aetosaurus in many cranial features, their close relationship as suggested by the present analysis, and the immature state of all available Aetosaurus specimens suggest two new alternative hypotheses: (1) Aetosaurus is the juvenile of a close relative of Paratypothorax or (2) it is itself the juvenile of Paratypothorax.